METHODS OF MANAGING THE FINANCIAL SITUATION OF BANKS - Jaloliddinovich , Rakhmatov Azizjon (PT ANTIS International Publisher, 2024)
Today, it is an urgent problem to study the methods of managing the financial situation of our commercial banks and introduce innovations. The article focuses on the methods of managing the financial situation of commercial banks and gives conclusions.